Zina sebagai Takdir: Analisis Kitab al-Minhāj fī Syarḥ Ṣaḥīḥ Muslim Karya Imam al-Nawawi : Zina as Destiny: Analysis of the Book of al-Minhāj fī Syarḥ Ṣaḥīḥ Muslim the Work of Imam al-Nawawi - Saputra, Doni (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
Zina is an act that is strictly prohibited in Islam. In a hadith, there is a narration that states that Allah SWT has destined some of Adam's children to commit adultery. However, in the Qur'an itself, Allah SWT forbids the act of adultery. Not only is it forbidden to approach her, but it is also considered a heinous act. So how is it possible for humans to avoid committing adultery, if Allah SWT has already destined some people to be adulterers? This research aims to uncover the meaning of the phrase